Synovial Fluid Eotaxin-1 Levels May Reflect Disease Progression in Primary Knee Osteoarthritis Among Elderly Han Chinese: A Cross-Sectional Study. (October 2019) - Li, Bei; Zhang, Yi-Li; Yu, Shou-Yi
Objective: The CC chemokine family member eotaxin-1, also named chemokine C-C motif ligand 11 (CCL11), has been detected in knee osteoarthritis (OA) and could induce breakdown of cartilage matrix. This study was performed to investigate the plasma and synovial fluid eotaxin-1 levels with the disease progression in elderly Han Chinese with primary knee OA. Design: A total of 143 elderly primary knee OA patients and 135 healthy controls were enrolled in the study. The Western Ontario and McMaster Universities Arthritis Index (WOMAC) was performed to evaluate the clinical severity. The radiographic severity was assessed by Kellgren-Lawrence (K-L) grading. Plasma and synovial fluid (SF) eotaxin-1 levels were explored using enzyme-linked immunosorbent assay. The SF levels of matrix metalloproteinase–3 (MMP-3) and interleukin-6 (IL-6) were also examined. Results: Elevated plasma eotaxin-1 levels were found in knee OA patients compared with healthy controls. Eotaxin-1 levels in SF of knee OA patients with K-L grade 4 were significantly elevated compared with those with K-L grades 2 and 3. Meanwhile, knee OA patients with K-L grade 3 had significantly increased SF levels of eotaxin-1 compared with those with K-L grade 2. Plasma eotaxin-1 levels in different K-L grading did not reach significant difference. Eotaxin-1 levels in SF of knee OA patients were significantly associated with disease severity evaluated by KL grading criteria. In addition, eotaxin-1 levels in SF were positively related to clinical severity illustrated by WOMAC as well as biochemical markers MMP-3 and IL-6. Conclusions: Eotaxin-1 levels in SF instead of plasma, were independently and positively related to the disease severity in elderly knee OA patients. The inhibition of eotaxin-1 and its related signaling pathways may serve as a novel therapeutic approach for OA progression.